Vegetation and Palynological Record in Sediments of the Camorim Dam, Pedra Branca State Park, Rio de Janeiro, Brazil - Barth, Ortrud Monika; Luz, Cynthia Fernandes Pinto da; Barros, Marcia Aguiar de; Misumi, Shana Yuri; Mello, Edson Farias (Anuário do Instituto de Geociências, 2023)
Pedra Branca State Park is situated near urban areas of Rio de Janeiro city. Several rivers descend towards the Atlantic Ocean and the damming of some ones, by the end of the 19th century, aimed to provide drinking water to the population. To the present day, Camorim dam is in operation and since its inception in 1908, the surrounding humid tropical forest has recovered, evidenced by the present palynological study of a core withdrawn from the dam’s northwestern part. The six analyzed levels showed pollen grains from botanical taxa characteristic of Rain Forest, Forest Pioneers, Campo vegetation, although less frequent, and Exotic plants. The palynomorphs concentration fluctuated throughout the core, which was attributed to a variation in sedimentation due to large floods that from time to time punished this region, but never decimated the forest around the Camorim dam and its contributing river basin.